Partnering With Patients in the Development and Lifecycle of Medicines: A Call for Action - Hoos, Anton; Anderson, James; Boutin, Marc; Dewulf, Lode; Geissler, Jan; Johnston, Graeme; Joos, Angelika; Metcalf, Marilyn; Regnante, Jeanne; Sargeant, Ifeanyi; Schneider, Roslyn F.; Todaro, Veronica; et al. (Therapeutic innovation & regulatory science, 2015)
The purpose of medicines is to improve patients' lives. Stakeholders involved in the development and lifecycle management of medicines agree that more effective patient involvement is needed to ensure that patient needs and priorities are identified and met. Despite the increasing number and scope of patient involvement initiatives, there is no accepted master framework for systematic patient involvement in industry-led medicines research and development, regulatory review, or market access decisions. Patient engagement is very productive in some indications, but inconsistent and fragmentary on a broader level. This often results in inefficient drug development, increasing evidence requirements, lack of patient-centered outcomes that address unmet medical needs and facilitate adherence, and consequently, lack of required therapeutic options and high costs to society and involved parties. Improved patient involvement can drive the development of innovative medicines that deliver more relevant and impactful patient outcomes and make medicine development faster, more efficient, and more productive. It can lead to better prioritization of early research; improved resource allocation; improved trial protocol designs that better reflect patient needs; and, by addressing potential barriers to patient participation, enhanced recruitment and retention. It may also improve trial conduct and lead to more focused, economically viable clinical trials. At launch and beyond, systematic patient involvement can also improve the ongoing benefit-risk assessment, ensure that public funds prioritize medicines of value to patients, and further the development of the medicine. Progress toward a universal framework for patient involvement requires a joint, precompetitive, and international approach by all stakeholders, working in true partnership to consolidate outputs from existing initiatives, identify gaps, and develop a comprehensive framework. It is essential that all stakeholders participate to drive adoption and implementation of the framework and to ensure that patients and their needs are embedded at the heart of medicines development and lifecycle management.